Ruthenium‐Alkylidene Complexes with Sterically Rigid Fluorinated NHC Ligands. Issue 43 (31st October 2018) - Masoud, Salekh M.; Akmalov, Timur R.; Palagin, Konstantin A.; Dolgushin, Fedor M.; Nefedov, Sergey E.; Osipov, Sergey N.
Abstract : An efficient procedure for the preparation of novel olefin metathesis catalysts of Grubbs‐Hoveyda type bearing sterically rigid NHC ligands has been developed. A preliminary evaluation of their catalytic activity has been performed on representative olefin metathesis reactions, such as RCM of malonates as well as self‐metathesis of allylbenzene. As result, it was found that along with excellent robustness, new complexes demonstrate remarkable activity in metathesis of allylbenzene, outperforming commercially available Grubbs‐Hoveyda catalyst in terms of yield and regioselectivity. Abstract : Novel ruthenium‐alkylidene complexes with sterically rigid fluorinated NHC ligands were synthesized and evaluated in representative olefin metathesis reactions. Along with excellent robustness, they demonstrate remarkable activity in self‐metathesis of allylbenzene, outperforming commercially available Grubbs‐Hoveyda catalyst in terms of yield and regioselectivity.